The effects of the Avellino Pumice eruption on the population of the Early Bronze age Campanian plain (Southern Italy) - Albore Livadie, Claude; Pearce, Mark; Delle Donne, Matteo; Pizzano, Natascia (Elsevier, 2018)
Palma Campania, the type-site of the Early Bronze Age Palma Campania culture, was covered by the products of the Avellino Pumice eruption, and was thus preserved in a similar way to the Roman sites in Campania covered by the AD 79 eruption. The devastating effects of this Plinian eruption led to the belief that it had killed a large part of the local population and/or caused large-scale emigration and landscape desertification. However, new sites have been found that were established shortly after the eruption and geoarchaeological studies of areas close to the Somma-Vesuvius volcano (Boscoreale, Boscotrecase, Torre Annunziata/Oplontis, Pompeii) and also further away (the Benevento area, Irpinia and the Salerno area) have shown continuity of occupation after the Avellino Pumice eruption and during the later, Middle Bronze Age, AP1 and AP2 eruptions. Palynological analysis also shows great similarity between the environments before and after the Avellino Pumice eruption. The pottery evidence is typologically very similar before and after the eruption, which suggests that the people who resettled the Campanian plain after the eruption were closely related to those living there previously, whose material culture is that of the Palma Campania culture. Radiocarbon dates also suggest a rapid recolonisation of some sites. In this paper we shall show that although the pyroclastic products of the Avellino Pumice eruption certainly had a major impact on the landscape (soils, flora, water resources) and may have killed off a percentage of the population in some areas, this eruption was not the main cause of the socio-economic and political transformations that occurred in this area during the Middle Bronze Age, which we believe to have been mainly caused by the cumulative effect of the later AP1 and AP2 eruptions